Opportunities and Challenges of the Religious Extension Profession in the Digital Age - Kibtyah, Maryatul; Mufidah, Dzurratul Lailil; Astuti, Nur Winda (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstrak: Perkembangan zaman yang semakin canggih, perkembangan iptek yang semakin modern, ditandai dengan penggunaan internet di dunia sudah sangat luar biasa. Pengguna aktif media sosial sekarang di Indonesia ini lebih dari 100 juta populasi dalam mengaksesnya. Media digital dengan segala kemudahan mendorong manusia mengalihkan aktivitas hidup melalui perangkat digital. Tidak terkecuali aktivitas keagamaan. Aspek-aspek sosial keagamaan dapat dilakukan melalui media digital di antaranya penyuluhan agama. Penyuluhan agama dapat dikatakan sebagian dari dakwah, yaitu proses penyampaian ajaran Islam yang dilakukan oleh seseorang yang memiliki keterampilan di bidangnya guna memberikan bimbingan dan penyuluhan baik berupa pembinaan ataupun pemberdayaan kepada masyarakat luas. Penyuluh agama menggunakan digital sebagai peluang untuk melakukan melakukan aktivitasnya terhadap masyarakat. Sekalipun menjadi tantangan tersendiri untuk profesi penyuluh agama yang mana harus benar-benar menguasi ilmunya. Dalam penelitian ini, peneliti menggunakan metode kualitatif deskriptif yang bertujuan untuk memahami peluang serta tantangan penyuluh di era digital.Abstract: The development of an increasingly sophisticated era, the development of increasingly modern science and technology, is marked by the use of the internet in the world which is extraordinary. Currently active users of social media in Indonesia have more than 100 million people accessing it. Digital media with all its convenience encourages people to divert their life activities through digital devices. Religious activities are no exception. Social and religious aspects can be carried out through digital media, including religious extension. Religious extension can be said to be part of da'wah, namely the process of conveying Islamic teachings carried out by someone who has skills in their field in order to provide guidance and extension in the form of guidance or empowerment to the wider community. Religious educators use digital as an opportunity to carry out their activities for the community. Even though it is a challenge in itself for the religious extension profession, which must really master its knowledge. In this research, researchers used a descriptive qualitative method which aims to understand the opportunities and challenges of extension workers in the digital age.